Profiling of known and novel microRNAs in an oleaginous crop native to the amazon basin, sacha inchi (Plukenetia volubilis), through smallRNA-Seq - Estrada Cañari, Richard; Rodriguez Perez, Lila Maciel; Romero Avila, Yolanda Madelein; Arteaga Chacon, Linda Rosemery; Ruelas Calloapaza, Domingo; Oha Humpiri, Filiberto; Flores, Nils; Coila , Pedro; Arbizu, Carlos (MDPI, 2025)
Background: MicroRNAs (miRNAs) play crucial roles in regulating tissue-specific gene expression and plant development. This study explores the identification and functional characterization of miRNAs in Plukenetia volubilis (sacha inchi), an economically and nutritionally significant crop native to the Amazon basin, across three organs: root, stem, and leaf. Methods: Small RNA libraries were sequenced on the Illumina Novaseq 6000 platform, yielding high-quality reads that facilitated the discovery of known and novel miRNAs using miRDeep-P. Results: A total of 277 miRNAs were identified, comprising 71 conserved and 206 novel miRNAs, across root, stem, and leaf tissues. In addition, differential expression analysis using DESeq2 identified distinct miRNAs exhibiting tissue-specific regulation. Notably, novel miRNAs like novel_1, novel_88, and novel_189 showed significant roles in processes such as auxin signaling, lignin biosynthesis, and stress response. Functional enrichment analysis of miRNA target genes revealed pathways related to hormonal regulation, structural reinforcement, and environmental adaptation, highlighting tissue-specific functions. The Principal Component Analysis and PERMANOVA confirmed clear segregation of miRNA expression profiles among tissues, underlining organ-specific regulation. Differential expression patterns emphasized unique regulatory roles in each organ: roots prioritized stress response and nutrient uptake, leaves focused on photosynthesis and UV protection, and stems contributed to structural integrity and nutrient transport, suggesting evolutionary adaptations in P. volubilis. Conclusions: This study identified novel miRNA-mediated networks that regulate developmental and adaptive processes in P. volubilis, underscoring its molecular adaptations for resilience and productivity. By characterizing both conserved and novel miRNAs, the findings lay a foundation for genetic improvement and molecular breeding strategies aimed at enhancing agronomic traits, stress tolerance, and the production of bioactive compounds.